Clinical and Laboratory Findings in Patients With Potential Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Reinfection, May–July 2020. (18th February 2021) - Lee, James T; Hesse, Elisabeth M; Paulin, Heather N; Datta, Deblina; Katz, Lee S; Talwar, Amish; Chang, Gregory; Galang, Romeo R; Harcourt, Jennifer L; Tamin, Azaibi; Thornburg, Natalie J; Wong, Karen K; et al.
Abstract: Background: We investigated patients with potential severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reinfection in the United States during May–July 2020. Methods: We conducted case finding for patients with potential SARS-CoV-2 reinfection through the Emerging Infections Network. Cases reported were screened for laboratory and clinical findings of potential reinfection followed by requests for medical records and laboratory specimens. Available medical records were abstracted to characterize patient demographics, comorbidities, clinical course, and laboratory test results. Submitted specimens underwent further testing, including reverse transcription polymerase chain reaction (RT-PCR), viral culture, whole genome sequencing, subgenomic RNA PCR, and testing for anti-SARS-CoV-2 total antibody. Results: Among 73 potential reinfection patients with available records, 30 patients had recurrent coronavirus disease 2019 (COVID-19) symptoms explained by alternative diagnoses with concurrent SARS-CoV-2 positive RT-PCR, 24 patients remained asymptomatic after recovery but had recurrent or persistent RT-PCR, and 19 patients had recurrent COVID-19 symptoms with concurrent SARS-CoV-2 positive RT-PCR but no alternative diagnoses. These 19 patients had symptom recurrence a median of 57 days after initial symptom onset (interquartile range: 47–76). Six of these patients had paired specimens available for further testing, but none had laboratory findings confirming reinfections. Testing of an additional 3 patients with recurrent symptoms and alternative diagnoses also did not confirm reinfection. Conclusions: We did not confirm SARS-CoV-2 reinfection within 90 days of the initial infection based on the clinical and laboratory characteristics of cases in this investigation. Our findings support current Centers for Disease Control and Prevention (CDC) guidance around quarantine and testing for patients who have recovered from COVID-19. Abstract : In an investigation of cases of potential severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reinfection, including laboratory testing of recovered patients who developed recurrent coronavirus disease 2019 (COVID-19) symptoms with positive reverse transcription polymerase chain reaction (RT-PCR) results for SARS-CoV-2, we did not confirm reinfection within the first 3 months after SARS-CoV-2 infection.